Fine-Scale Population Admixture Landscape of Tai–Kadai-Speaking Maonan in Southwest China Inferred From Genome-Wide SNP Data - Chen, Jing; He, Guanglin; Ren, Zheng; Wang, Qiyan; Liu, Yubo; Zhang, Hongling; Yang, Meiqing; Zhang, Han; Ji, Jingyan; Zhao, Jing; Guo, Jianxin; Chen, Jinwen; et al. (Frontiers in Genetics, 2022)
Guizhou Province harbors extensive ethnolinguistic and cultural diversity with Sino-Tibetan-, Hmong–Mien-, and Tai–Kadai-speaking populations. However, previous genetic analyses mainly focused on the genetic admixture history of the former two linguistic groups. The admixture history of Tai–Kadai-speaking populations in Guizhou needed to be characterized further. Thus, we genotyped genome-wide SNP data from 41 Tai–Kadai-speaking Maonan people and made a comprehensive population genetic analysis to explore their genetic origin and admixture history based on the pattern of the sharing alleles and haplotypes. We found a genetic affinity among geographically different Tai–Kadai-speaking populations, especially for Guizhou Maonan people and reference Maonan from Guangxi. Furthermore, formal tests based on the f3/f4-statistics further identified an adjacent connection between Maonan and geographically adjacent Hmong–Mien and Sino-Tibetan people, which was consistent with their historically documented shared material culture (Zhang et al., iScience, 2020, 23, 101032). Fitted qpAdm-based two-way admixture models with ancestral sources from northern and southern East Asians demonstrated that Maonan people were an admixed population with primary ancestry related to Guangxi historical people and a minor proportion of ancestry from Northeast Asians, consistent with their linguistically supported southern China origin. Here, we presented the landscape of genetic structure and diversity of Maonan people and a simple demographic model for their evolutionary process. Further whole-genome-sequence–based projects can be presented with more detailed information about the population history and adaptative history of the Guizhou Maonan people.